MANAGEMENT OF LATENT TO ACTIVE PERIOD ON DELIVERY ADVANCEMENT - DINI KURNIAWATI (NURSCOPE: Jurnal Penelitian dan Pemikiran Ilmiah Keperawatan, 2017)
The first stage of labor to the complete dilatation of the cervix consists of two phases , latent (dilatation 1 cm to 3 cm) and active phases ( 4 cm to 10 cm). Latent phase has a longer duration of the active phase, so more obstetric interventions than those admitted in the this phase. Intervention and duration of the latent phase will cause discomfort and anxiety in the mother during this phase of waiting for progress. Increasing the number of interventions at this phase can be caused by a diagnosis or assessment is less precise and cause complications. Complications in this phase causes of postpartum hemorrhage, chorioamnionitis, and neonatal risk. Interventions at latent phase include oxytocin, amniotic rupture membranes (amniotomy). Woman with prolonged latent phase intervention such as caesarean section (SC). In this phase is need management intervention to reduce the discomfort.Key Word : latent phase, active phase, intervention management, labor